Application of Unplugged Computer Science Based on Ethnopedagogy as a Teaching Alternative in Basic Programming Algorithms Subjects - Bara M. Buana; Lala S. Riza; Asep Wahyudin (Journal of Computers for Society, 2023)
This research is motivated by the lack of equal distribution of technology in regions of Indonesia, including Papua, Sulawesi and even Java, which is still not evenly distributed, so that technology education in some areas is difficult to progress and develop. Therefore, the aim of this research is to design and implement Ethnopedagogy-based Unplugged Computer Science (UCS), creating animation-based media as documentation to make it easier for teachers to understand UCS. The UCS method is a method for teaching computers without using computers and is based on ethnopedagogy, so technology learning can be done using cultural elements, both traditional tools and traditional games from a region in Indonesia. In designing Ethnopedagogy-based UCS, 4 stages are carried out, namely compiling the material, determining the ethnopedagogy tools or games that will be used, mapping the material as well as abstracting ideas for ethnopedagogy-based UCS and preparing steps for Ethnopedagogy-based UCS that will be carried out by teachers and students. The waterfall method is used as a reference for creating animated media as documentation of Ethnopedagogy-based UCS.